Script Knowledge and the Felicity of Phase Particles in German Adjectival Passives. (15th August 2018) - Irmer, Matthias; Mueller-Reichau, Olav
Abstract: This paper examines the conditions under which the temporal expression immer noch ("still") and related phase particles are allowed or excluded in German adjectival passive sentences. A detailed discussion of the phenomenon is provided, and it is argued that not only the semantics of involved linguistic expressions and constructions, but also background script knowledge must be taken into account to fully understand the combinatorics. A notion of scripts is developed as a finite sequence of cognitive frames, where one frame precedes and provides an occasion for the next one. The paper determines a new condition for the exclusion of immer noch that up to now went unnoticed. Specifically, it is claimed that adjectival passives denoting the result state of a script-final event cannot be combined with immer noch due to conflicting inferences. The proposed integration of linguistic material with background frame and script knowledge is based on the central assumption that event kinds correspond to frames, which opens up a new perspective on the relation between conceptual structure and compositional semantics.